Detecting autonomic dysfunction in patients with glaucoma using dynamic pupillometry - Park, Hae-Young Lopilly (Medicine (Baltimore), 2019)
Autonomic dysfunction is a feature of glaucoma patients, which are reported to be related to glaucoma progression. We investigated pupil responses to a light flash using dynamic pupillometry in glaucoma patients to assess autonomic nervous system status. In total, 97 glaucoma patients, including 21 eyes of 21 glaucoma patients with cardiac autonomic dysfunction, were enrolled. Pupil reactions were assessed using 1 flash of white light after 2 minutes of dark adaptation and recorded using dynamic pupillometry. Changes in the radius of the pupil were evaluated as a function of several time-dependent and pupil/iris (P/I) diameter ratio parameters. Autonomic function was assessed using a cardiac heart-rate-variability test which performs 5 autonomic function tests and classifies patients with cardiac autonomic neuropathy (CAN). Comparison of pupil parameters between eyes with and without disc hemorrhage indicated larger P/I ratios in darkness, greater changes in the P/I ratio during examination, shorter latency to plateau, and shorter duration of constriction in eyes with disc hemorrhages. A comparison of pupil parameters between eyes with and without CAN showed larger P/I ratios in darkness, larger P/I ratios at maximum constriction, and prolonged latency to maximum constriction. The presence of CAN was significantly related to the P/I ratio in darkness and the latency of maximum constriction. Using dynamic pupillometry, we found that glaucoma patients with CAN dysfunction have larger baseline pupils in darkness and different constriction responses to light. Assessing the pupils might be a good method of identifying patients with autonomic dysfunction.